2021
DOI: 10.21203/rs.3.rs-136310/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of curcumin and its nanomicelle form on body weight, insulin resistance, adiponectin, and blood parameters of streptozotocin-induced diabetic rats

Abstract: Curcumin can be used for diabetes treatment. However, it rapidly degrades and has low absorption in gastrointestinal system. Its nanomicelle form might improve its efficiency. Therefore, they both assessed in streptozotocin-induced diabetic rats. Fifty male wistar rats were induced diabetes and divided into 5 groups and treated with 1) no dietary supplement, 2 and 3) 40 and 80 mg/kg curcumin, 4 and 5) 40 and 80 mg/kg nanomicelle curcumin. A group of 10 untreated rats was considered as healthy control. Serum co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…16,17 An increase of QUICKI value was also reported in patients with T2DM on a clinical trial after curcumin intake, as an addition to the previously mentioned effect. Findings regarding glycemic indices in our study are in line with Dadgar et al 18 , that has reported a significant suppressing effect of curcumin nano micelles on levels of serum glucose concentration in streptozotocininduced diabetic rats. This report is consistent with the original research results carried out so far, as mentioned by Rivera-Mancia et al 19 , about the utility of curcumin to reduce insulin resistance by targeting the JNK/ IRS pathway that has been tested in several in vivo and in vitro models.…”
Section: Discussionsupporting
confidence: 93%
“…16,17 An increase of QUICKI value was also reported in patients with T2DM on a clinical trial after curcumin intake, as an addition to the previously mentioned effect. Findings regarding glycemic indices in our study are in line with Dadgar et al 18 , that has reported a significant suppressing effect of curcumin nano micelles on levels of serum glucose concentration in streptozotocininduced diabetic rats. This report is consistent with the original research results carried out so far, as mentioned by Rivera-Mancia et al 19 , about the utility of curcumin to reduce insulin resistance by targeting the JNK/ IRS pathway that has been tested in several in vivo and in vitro models.…”
Section: Discussionsupporting
confidence: 93%
“…Curcumin loaded nanomicelles were targeted to insulin resistant male Wister rats. Curcumin from a nano platform showed significant outcomes (improved insulin resistance) in the treatment of insulin resistance and diabetes mellitus [110]. A recent study on phytochemicals has shown that curcumin is actively involved in decreasing insulin resistance, HbA1c and fasting insulin, leading to effective diabetes management [111].…”
Section: Role Of Curcumin Targeting Inflammation In Diabetes Resistancementioning
confidence: 99%